Mobilising The Shared Service Centre In A Highly Centralised Power Context: An Interpretive Case Study Of A Chinese State-Owned Enterprise - You, Kun (2024)
This thesis presents an interpretive case study of a Chinese State-Owned Enterprise (SOE) namely Sinopec which has mobilised a Shared Service Centre (SSC) by overcoming the resistance to change (silently rejecting the SSC model imposed by the Chinese government). Following the reform of Chinese state-owned enterprises (SOEs), introduced by the Chinese State-owned Assets Supervision and Administration Commission (SASAC) in 2013, China has witnessed the mushrooming of SSC to improve efficiency and create competitive competency through cost savings and improved product quality. However, as a management model that originated in the West, the practice of SSC in SOEs has experienced resistance to change, mainly due to the influence of the unique Chinese institutions, Confucian culture and the complexity of SSC concerning process reengineering. Therefore, this study seeks to explain and analyse the process of SSC mobilisation and evolution in the highly power-centralised context and the roles and interactions of its special actors (e.g., party secretaries and Confucian culture) in this process by drawing on the concepts rooted in actor-network theory (ANT) and using semi-structured interviews, documentary analysis and observation. This thesis reveals that the effective mobilisation of SSC does not follow a linear process guided by ‘critical success factors’. Instead, it entails a continuous ‘spiral’ of interactions and compromises involving both human and non-human actors. Power provides the core actor, acting as an orchestrator, with legitimacy and formality, thereby reducing resistance and obstacles during the translation process for SSC mobilisation. The findings of the thesis also indicate that Confucian culture actively contributes to the SSC mobilisation and facilitates interaction among diverse actors, allowing them to pursue their interests and requirements while focusing on the collective interests and deferring to the power of the core actor.